Bio‐Inspired Artificial Vision and Neuromorphic Image Processing Devices (Adv. Mater. Technol. 2/2022). Issue 2 (8th February 2022) - Kim, Min Sung; Kim, Min Seok; Lee, Gil Ju; Sunwoo, Sung‐Hyuk; Chang, Sehui; Song, Young Min; Kim, Dae‐Hyeong
Abstract : Efficient Image Recognition In article number 2100144, Young Min Song, Dae‐Hyeong Kim, and colleagues present remarkable technological advances in terms of the efficient image recognition. These achievements are due in large to the recent development in the bio‐inspired artificial vision and the neuromorphic image processing devices.